Behavior in the elevated plus maze is differentially affected by testing conditions in rats under and over three weeks of age - Albani, Sarah H.; Andrawis, Marina M.; Abella, Rio Jeane H.; Fulghum, John T.; Vafamand, Naghmeh; Dumas, Theodore C. (Frontiers in Behavioral Neuroscience, 2015)
The late postnatal period in rats is marked by numerous changes in perceptual and cognitive abilities. As such, age-related variation in cognitive test performance might result in part from disparate sensitivities to environmental factors. To better understand how testing conditions might interact with age, we assessed anxiety behavior on an elevated plus maze in juvenile rats around three weeks of age under diverse testing conditions. Plasma corticosterone and neuronal activation patterns in the forebrain were examined after maze exposure. We found that anxiety was differentially expressed during different stages of late postnatal development. Bright illumination and morning testing encouraged greatest open arm exploration on the elevated plus maze in younger animals, while older rats explored open areas more under dim illumination in the morning compared to bright illumination in the afternoon/evening. Older rats exhibited higher plasma corticosterone levels at baseline compared to younger rats; however, this trend was reversed for post-testing corticosterone. Additionally, post-testing corticosterone levels were inversely related to time of testing. Compared to testing in the morning, elevated plus maze exposure in the afternoon/evening elicited greater neuronal Arc expression in the amygdala. Arc expression in the amygdala after morning testing was greater at P22-24 than P17-19. In layer 2/3 of primary visual cortex, Arc expression was elevated in younger animals and age interacted with time of testing to produce opposing effects at P17-19 and P22-24. These data suggest that age-related differences in anxiety-associated behavior during the late postnatal period are due in part to changes in light sensitivity and emergence of a circadian cycle for corticosterone. The findings illustrate that late postnatal behavioral development in rodents is a complex orchestration of changes in neural systems involved in perception, cognition, affect and homeostatic regulation.